Synthesis, Characterization and DNA-Binding of Cobalt(II) Complex with 3-Benzyl-4-(p-hydroxy-m-methoxybenzylidenamino)-1H-1,2,4-triazole-5-one - Arslantas, Ali; Isiklar, Mustafa; Yuksek, Haydar (Asian Journal of Chemistry, 2011)
In this work, the synthesis, characterization and DNA-binding of cobalt(II) complex with 3- benzyl-4-(p-hydroxy-m-methoxy-benzylidenamino)-1H-1,2,4-triazole-5-one has been reported. The newly prepared compound was characterized by elemental analyses, IR, UV-vis, 1H NMR spectra. The interaction of the Co(II) complex with cat DNA was investigated by UV absorption spectroscopy and viscosity measurements. The binding constant of the complexe was determined using absorption measurement and found to be 0.98 × 104 M-1. Results suggest that the complex binds to DNA via an intercalative binding mode.